2011
DOI: 10.1007/s11418-011-0509-y
|View full text |Cite
|
Sign up to set email alerts
|

Active components from Siberian ginseng (Eleutherococcus senticosus) for protection of amyloid β(25–35)-induced neuritic atrophy in cultured rat cortical neurons

Abstract: Not only neuronal death but also neuritic atrophy and synaptic loss underlie the pathogenesis of Alzheimer's disease as direct causes of the memory deficit. Extracts of Siberian ginseng (the rhizome of Eleutherococcus senticosus) were shown to have protective effects on the regeneration of neurites and the reconstruction of synapses in rat cultured cortical neurons damaged by amyloid β (Aβ)(25-35), and eleutheroside B was one of the active constituents. In this study, a comprehensive evaluation of constituents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…It was confirmed that IF can interact with human serum albumin through the use of a fluorescence method in combination with Fourier transform infrared and circular dichroism spectroscopy techniques [23]. IF is one of the active compounds in Siberian ginseng (Eleutherococcus senticosus), a plant that is strongly protective against amyloid β (25-35)-induced neuritic atrophy in cultured rat cortical neurons [24]. IF has inhibitory effects on iNOS protein expression and NO generation.…”
Section: Introductionmentioning
confidence: 90%
“…It was confirmed that IF can interact with human serum albumin through the use of a fluorescence method in combination with Fourier transform infrared and circular dichroism spectroscopy techniques [23]. IF is one of the active compounds in Siberian ginseng (Eleutherococcus senticosus), a plant that is strongly protective against amyloid β (25-35)-induced neuritic atrophy in cultured rat cortical neurons [24]. IF has inhibitory effects on iNOS protein expression and NO generation.…”
Section: Introductionmentioning
confidence: 90%
“…Numerous reports have addressed that AS could also exert therapeutic effects against neurodegenerative diseases, such as Parkinson's disease (Li et al, 2014;Liu et al, 2012) and Alzheimer's disease (Xu et al, 2008). AS contains various bioactive components (WHO, 2004), which could protect PC12 cells against neurotoxin damage (Lu et al, 2011), and ameliorate neuritic atrophy induced by amyloid beta (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in cultured rat cortical neurons (Bai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…17406004 in 2005-2007 and No. 21406004 in 2009-2011 from Japan Society for the Promotion of Science, by a grant (KH31025, KHB1005) from the Japan Health Sciences Foundation, and by Expansion Program, Regional Innovation Cluster Program, Global Type (II) from the Ministry of Education, Culture, Sports, Science and Technology, Japan.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Moreover, the major constituents such as eleutheroside B (EB) had anti-fatigue and antioxidant effects, NGF-like effect in cultured PC12 cell (Davydov & Krikorian, 2000;Tasugi et al, 1985;Yamazaki, Hirota, Chiba, & Mohri, 1994), eleutheroside E (EE) possessed anti-stress and anti-fatigue effects, inhibition of gastric ulcer, and NGF-like effect in cultured PC12 cell (Davydov & Krikorian, 2000;Fujikawa, Yamaguchi, Morita, Takeda, & Nishibe, 1996;Nishibe, Inoshita, Takeda, & Okano, 1990;Yamazaki et al, 1994) and isofraxidin (IF) had antidepressant activity et al (Chen & Liu, 1991;Davydov & Krikorian, 2000). Our previous study showed that the water and methanol extracts of SG had trophic and benefit effects on neurite outgrowth, synapse formation and neuronal protection in in vitro assay system for Alzheimer's disease, and eleutheroside B was one of the active constituents (Bai, Tohda, Zhu, Hattori, & Komatsu, 2011;Tohda et al, 2008). These evidences have corroborated the usefulness and benefits of SG.…”
Section: Introductionmentioning
confidence: 99%